Spinal Muscular Atrophy Patient iPSC-Derived Motor Neurons Have Reduced Expression of Proteins Important in Neuronal Development - Fuller, Heidi R.; Mandefro, Berhan; Shirran, Sally L.; Gross, Andrew R.; Kaus, Anjoscha S.; Botting, Catherine H.; Morris, Glenn E.; Sareen, Dhruv (Frontiers in Cellular Neuroscience, 2016)
Spinal muscular atrophy (SMA) is an inherited neuromuscular disease primarily characterized by degeneration of spinal motor neurons, and caused by reduced levels of the SMN protein. Previous studies to understand the proteomic consequences of reduced SMN have mostly utilized patient fibroblasts and animal models. We have derived human motor neurons from type I SMA and healthy controls by creating their induced pluripotent stem cells (iPSCs). Quantitative mass spectrometry of these cells revealed increased expression of 63 proteins in control motor neurons compared to respective fibroblasts, whereas 30 proteins were increased in SMA motor neurons versus their fibroblasts. Notably, UBA1 was significantly decreased in SMA motor neurons, supporting evidence for ubiquitin pathway defects. Subcellular distribution of UBA1 was predominantly cytoplasmic in SMA motor neurons in contrast to nuclear in control motor neurons; suggestive of neurodevelopmental abnormalities. Many of the proteins that were decreased in SMA motor neurons, including beta III-tubulin and UCHL1, were associated with neurodevelopment and differentiation. These neuron-specific consequences of SMN depletion were not evident in fibroblasts, highlighting the importance of iPSC technology. The proteomic profiles identified here provide a useful resource to explore the molecular consequences of reduced SMN in motor neurons, and for the identification of novel biomarker and therapeutic targets for SMA.